Pengaruh Komunikasi, Motivasi, dan Komitmen Terhadap Kinerja Karyawan Pada PT. Nan Darma Kanigara - Zebua, Septin Hartati; Saputro, Arie Hendra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
In an increasingly competitive world, employee performance is one of the key factors determining the success of a company. Optimal employee performance is not only influenced by individual abilities and skills, but also by psychological and social factors in the work environment. This study aims to determine the Effect of Communication, Motivation, and Commitment on Employee Performance at PT. Nan Darma Kanigara. The research method used is a quantitative method with a descriptive verification approach. The population sample studied consisted of 39 employees of PT. Nan Darma Kanigara. Measurement in the questionnaire used a 5-item Likert scale. The data analysis technique in this study used the SPSS v26 software application with the path analysis method. The results of this study indicate that Communication, Motivation, and Commitment have a positive and significant effect on Employee Performance at PT. Nan Darma Kanigara simultaneously and Based on the output results obtained, it can be concluded that the R square value is 0.526, which means 52.6% of Employee Performance at PT. Nan Darma Kanigara is influenced by the variables Communication, Motivation, and Commitment. Meanwhile, the remaining 47.4% is influenced by other variables not discussed in this study.